Method of VC6.0 Programming Client Accessing to OPC Server of KingView - WEI Sen-sheng; TIAN Mu-qi (Gong-kuang zidonghua, 2012)
The paper introduced architecture principles of OPC technology and programming methods of OPC client, and put forward a method of OPC client program to use customized interface to access data. It designed OPC client application program with VC6.0 programming, and introduced implementation steps of OPC client application program in details. Using KingView as OPC server, the method achieves data exchange between OPC client program and KingView OPC server by OPC interface to access variable data in database.